Bilateral Breast Masses with a Rare Etiology - Friederike Thieringer; Gideon Sartorius; Katrin Kalf; Viola Heinzelmann; Marcus Vetter (Case Reports in Oncological Medicine)
Breast masses have a variety of benign and malignant etiologies. We present the case of a 28-year-old woman with bilateral large painful breast masses that developed rapidly in the three weeks before first presentation. Further investigation revealed bilateral ovarian masses. Biopsies of both ovarian masses were taken, and the pathology reported Burkitt’s lymphoma. Additional staging with a PET scan was suggestive of bone marrow involvement, but bone marrow biopsy was negative. Examination of the cerebrospinal fluid did not identify malignant cells. The patient underwent CODOX-M/IVAC chemotherapy, and a complete response was demonstrated after one cycle of treatment. Six months after finishing chemotherapy the patient remained in complete remission. To our knowledge this is the first case reporting simultaneous involvement of breast, ovaries, and bones in Burkitt’s lymphoma. Gynecologists and oncologists should be aware of this pattern. Polychemotherapy treatment must be initiated rapidly with curative intent.